Epidemiological Characteristics of Human Rabies in Urban and Suburban Districts in Shanghai, 2006–2021 - Zhi Li; Jiayu Hu; Zhuoying Huang; Xiang Guo; Jia Ren; Jing Qiu; Xiaoying Ma; Han Yan; Fang Huang; Xiaodong Sun (Zoonoses)
Rabies is a vaccine-preventable, viral zoonotic disease caused by a lyssavirus. This study was aimed at analyzing the epidemiological characteristics of human rabies in Shanghai to provide valuable information to support accurate prevention and control. Individual-level data on human rabies and dog bites/attacks in Shanghai were collected from 2006 to 2021. Demographic characteristics, spatial and seasonal patterns, and correlations were analyzed to explore the epidemiological profiles. Infection risk was predicted with a Bayesian aggression model. A total of 43 human rabies cases were registered in Shanghai in 2006–2021; the annual average incidence rate was 0.01/100000. Males and residents at ages of 10 to 19 years and over 50 years had an elevated risk of rabies. All cases were reported in suburban districts and peaked in July. The body parts most frequently injured by dogs were the hands (48.84%). The fatality rate was 100%. Most cases (86.05%) were not treated after exposure. A total of 310 dog bites/attacks were reported and significantly correlated with the number of cases (P=0.010). The predicted risk of human rabies was higher in suburban than urban areas. The incidence of human rabies in Shanghai was relatively low; nevertheless, risk still existed, particularly in suburban areas.